Intervention for Pressure Injuries Prevention in Bed Rest Patients - Nur Chayati; Sinta Yudistia Nurachman (Institute of Computer Science (IOCS), 2023)
Pressure injuries, also known as pressure injuries or hospital-acquired pressure injuries, was damage to the integrity of the skin or soft tissue in a local area that tends to compress the bony prominences with the surface area due to a combination of prolonged pressure such as friction, shear and moisture. The main groups at risk for pressure injuries were patients with spinal cord injuries, hospitalized patients, especially those undergoing orthopedic surgery and patients admitted to the intensive care unit (ICU). The purpose was to determine the types of tools, materials, techniques and nursing interventions for the prevention of pressure injuries in bed rest patients. The research used a literature review using 3 databases, namely Science direct, Pudmed, Google Scholer with studies design included Quasi Experimental and Romdomized Controlled Trials. The study obtained 7 articles describing pressure ulcer prevention interventions such as providing bed rest, giving oral supplements, providing massage therapy and lubricating agents, providing moisturizers in the wound area and providing appropriate mattresses for bed rest patients.